2003
DOI: 10.4049/jimmunol.171.8.4311
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Molecule Immune Enhancement in a Plasmid Vaccine Model Is Regulated in Part Through the Ig Constant-Like Domain of CD80/86

Abstract: There is great interest in understanding the role of costimulatory molecules in immune activation. In both the influenza and HIV DNA immunization models, several groups have reported that coimmunization of mice with plasmids encoding immunogen and CD86, but not CD80, effectively boosts Ag-specific T cell activation. This difference in immune priming provided an opportunity to examine the functional importance of different regions of the B.7 molecules in immune activation. To examine this issue, we developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Findings from our laboratory have shown that the addition of molecular adjuvants may not only increase the overall breadth and magnitude of immune responses but may also skew the type of immune response seen in vivo. [86,87] One of the cytokines we initially reported on is interleukin 12 (IL-12), a pro-inflammatory cytokine mainly secreted by DCs. Other immune cells such as macrophages and Bcells may also secrete IL-12.…”
Section: Molecular Adjuvants For Dna Vaccinesmentioning
confidence: 99%
“…Findings from our laboratory have shown that the addition of molecular adjuvants may not only increase the overall breadth and magnitude of immune responses but may also skew the type of immune response seen in vivo. [86,87] One of the cytokines we initially reported on is interleukin 12 (IL-12), a pro-inflammatory cytokine mainly secreted by DCs. Other immune cells such as macrophages and Bcells may also secrete IL-12.…”
Section: Molecular Adjuvants For Dna Vaccinesmentioning
confidence: 99%
“…The use of genetic adjuvants to enhance immune responses in CCHF vaccine development has been sparsely investigated. Plasmid-expressing cytokines such as interferon-c, interleukin (IL)-2, IL-12, Granulocyte/ macrophage colony-stimulating factor, 120-122 chemokines MIP-1a and RANTES, 123,124 and ICAM-1, CD40L, and CD80/86 costimulatory molecules, [125][126][127] have been investigated as genetic adjuvants in vivo with promising results in different settings. In the sole CCHF vaccine study using genetic adjuvants described in the literature, the CD24 costimulatory molecule was codelivered with the CCHFV NP.…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%
“…CD80 and CD86 are ligands of CD28/CTLA4 and may have different functions [ 29 ]: although both CD80 and CD86 activate effector T cells, CD80 seems to be especially important for the stimulation of T regulatory cells and, therefore, the inhibition of the immune response. Indeed, DNA immunization with plasmids encoding CD80 induces weaker responses than with plasmids encoding CD86 [ 30 ]. In diabetic mice and in lupus-prone MRL/ lpr mice, the blockade of CD80 worsens the severity of both diseases, whereas blockade of CD86 prevents diabetes and has mild effects on lupus [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%